KEMAMPUAN MENULIS DESKRIPSI (STUDI KASUS DI PONDOK PESANTREN NUURUSSHIDDIIQ, CIREBON) - Ririen Wardiani; Indrya Mulyaningsih (Indonesian Language Education and Literature, 2015)
This study aimed to describe the writing skills of the students at the boarding school in terms of form and rules of Indonesian. This research strategy using case studies from August to November 2013. Data selected with purposive sampling techniques consisting of, 15 male students and 15 female students. Data were collected through: 1) observation, 2) interview, 3) sheets of observations, and 4) test. Validity reached by: 1) triangulation of data sources, 2) triangulation of data collection methods, and 3) review of informant. Data analysis use traditional two stages, ie, classifying and interactive analysis model of Miles. The results are: 1) the students do not understand the type or form of composition description; 2) there are errors on: (a) the use of capital letters, (b) the use of letters or italics, (c) the use of punctuation comma, (d) condensation said, (e) writing 'di' as preposition and 'di' as affix, and (f) writing the correct word in accordance EYD; 3) students do not understand the process of forming a word; 4) students have not been able to write a sentence properly and effectively; and 5) students do not understand and pay attention to the meaning of sentences.